(untitled) (Research, Society and Development, 2022)
Procurement management is critical to organizations in order to be efficient and effective in hiring products and services. With the high demand for financing companies seek more effective contracting, with outsourcing of services is increasing, companies seek the specific areas with the outsourcing of specialized companies thus guaranteeing the desired result. Procurement management addresses the procurement of products and services external to the project team. It can be subdivided into four sub-processes: plan the management of the acquisitions; conducting acquisitions; control acquisitions and close acquisitions. Make sure all steps work together. The present study has as main objective to approach on the management of acquisitions in the management of projects, through the case study for the implantation of an industrial process of treatment of oils and fats. It demonstrates the application of procurement management techniques in a case study to show management success as well as the translation of the organization’s strategic objectives into projects so that, in fact, the desired results are achieved. It is concluded that what has been accomplished in the field by the organization is following the good practices of the PMBOK guide, using all the processes of planning, conducting, controlling, and closing and with this has demonstrated that the efficiency in the acquisition management has benefited the project like everything.